Estudo da eficiência agronômica de diferentes fontes de fosfato na cultura do milho (Zea mays L). - Nascimento, Bruno Lucio Meneses (2013)
The efficiency of a phosphate fertilizer is correlated positively with both the plant growth and production, in other words, the more efficient is the fertilizer, the greater the gains in crop growth and production. Among the various phosphorus sources used to enrich the soil there are natural phosphates of low solubility and industrial phosphates of high solubility. The high costs of the imported soluble fertilizers containing phosphorus is one of the reason that have made many countries to begin to use the natural rock phosphates in order to improve and reduce the costs of agricultural production. Therefore, the objective of this work was to evaluate agronomic efficiency of different phosphorus sources, which included the phosphate of Tocantins (FNT), reactive phosphate of Tunisia (FNR), rock phosphate Bahia (FNB) and triple superphosphate (TSP), where their effects on growth of corn under greenhouse conditions were studied. The study was conducted in a completely randomized block design and arranged in a factorial arrangement 4x4, with 4 rates of phosphorus (0, 100, 200 and 300 mg P kg-1), 4 different P sources (FNT FNR, FNB and SFT) and with 4 replications. Therefore, the experiment consisted of 16 treatments, totalizing 64 pots as experimental units. The lower both heights and stalk diameter were obtained when the corn was fertilized with rock phosphate; differently occurred in the treatment in which was used the triple superphosphate, where were found the greatest heights and the largest stalk diameters. By analyzing the averages of the amounts of nutrients absorbed by corn fertilized with triple superphosphate, FNB, FNT and FNR, it was noted that the decreasing order of nutrient absorption was as follows: K> N> P> Mg> S> Ca, K> N> Ca> P> Mg> S, K> N> Ca> Mg> P> S, K> N> Mg> Ca> P> S, respectively. By analyzing the agronomic efficiency values for the 4 P sources applied to corn, it was found that they occurred in a descending order: Triple superphosphate> FNB> FNR> FNT.